Damping, corrosion-resistant and wear-resistant elevator hoisting machine base coating and preparation method thereof
Patent Information
- Application Number
- CN202611124908.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-28
AI Technical Summary
然而,这些填料在实际应用中面临两大关键技术难题:一是填料易团聚,由于纳米/微米尺度的填料表面能高,在基体中难以均匀分散,团聚体反而成为涂层中的缺陷点,降低力学强度和阻隔性能;二是填料与基体界面结合弱,未改性填料表面呈惰性,与有机树脂基体仅依靠物理吸附作用,界面结合力差,在外力作用下易发生脱粘,导致填料无法有效传递和耗散能量
(1)构建类枝蔓结构填料,实现填料-基体一体化:本发明通过对零维、一维、二维填料分别进行改性处理,成功构建了类枝蔓结构填料。该结构将零维的点状填料、一维的线状填料和二维的片状填料通过化学键合与非共价相互作用连接成三维网络,实现了填料在基体中的均匀分散和稳定锚定,从根本上解决了传统填料易团聚、界面结合弱的技术难题。
Smart Images

Figure CN122628653B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of elevator vibration reduction technology, specifically relating to a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base and its preparation. Background Technology
[0002] With the continuous advancement of urbanization in my country, the number of high-rise buildings is rapidly increasing, and elevators, as an indispensable vertical transportation tool in modern buildings, are experiencing a sustained growth in their number. The operational safety and passenger comfort of elevators have become important indicators for measuring building quality. However, as a typical electromechanical integrated device, elevators inevitably generate vibration and noise during operation. The traction machine, as the power core of the elevator, transmits structural vibrations through its base to the building structure, causing floor vibrations and structural noise, directly affecting the passenger experience and potentially causing long-term disturbance to the quality of life of surrounding residents. Therefore, effectively controlling the vibration transmission generated by the elevator traction machine is of great significance for improving the overall performance of elevator products.
[0003] To address the protection and vibration reduction requirements of elevator traction machine bases, various coating materials have been researched and applied in existing technologies. For example, while epoxy resin-based anti-corrosion coatings offer good chemical corrosion resistance, their damping performance is poor, making it difficult to effectively dissipate vibration energy. Polyurethane elastic coatings have a certain vibration reduction effect, but their wear resistance and aging resistance are insufficient, and they are prone to powdering and cracking after long-term use. Inorganic zinc-rich coatings possess excellent anti-corrosion properties, but their high rigidity limits their vibration reduction effect. Furthermore, although there are reports of multi-layer composite coatings in existing technologies, the functional layers are mostly simply stacked, resulting in insufficient interfacial bonding strength. Under dynamic loads, interlayer delamination easily occurs, leading to functional failure.
[0004] To improve the overall performance of coatings, existing technologies attempt to introduce functional fillers into the coating matrix, such as zero-dimensional nanoparticles, one-dimensional fibers or whiskers, and two-dimensional sheet materials. However, these fillers face two major technical challenges in practical applications: First, the fillers are prone to agglomeration. Due to the high surface energy of nano / micro-scale fillers, they are difficult to disperse uniformly in the matrix, and agglomerates become defects in the coating, reducing mechanical strength and barrier properties. Second, the interfacial bonding between the filler and the matrix is weak. Unmodified filler surfaces are inert and rely solely on physical adsorption with the organic resin matrix, resulting in poor interfacial bonding. Under external forces, they are prone to debonding, preventing the filler from effectively transferring and dissipating energy. These problems make it difficult for single-dimensional fillers to form an effective synergistic enhancement effect in the coating, failing to simultaneously meet the comprehensive requirements of traction machine bases for vibration reduction, corrosion resistance, and wear resistance. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a vibration-damping, corrosion-resistant, and wear-resistant coating for elevator traction machine bases, its preparation method, and its application.
[0006] The objective of this invention is achieved through the following technical solution: The first aspect of this invention is to provide a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base. The coating covers the surface of a substrate and has a double-layer composite structure. From the inside to the outside of the substrate surface, the coating sequentially includes a vibration-damping layer and a corrosion-resistant and wear-resistant layer. By weight, the raw materials of the vibration-damping layer include 70-80 parts of a vibration-damping layer base material, 10-15 parts of a dendritic filler, 1-2.5 parts of a wetting agent, 1-3 parts of a defoamer, 1.5-2 parts of a dispersant, and 90-125 parts of deionized water. The vibration-damping layer base material is one of a polyurethane-based IPN emulsion, an epoxy resin-based IPN emulsion, an acrylate-based IPN emulsion, a silicone-based IPN emulsion, and a fluoropolymer-based IPN emulsion. The raw materials of the corrosion-resistant and wear-resistant layer include a corrosion-resistant and wear-resistant layer base material. The material comprises 30-40 parts of a dendritic structure filler, 5-10 parts of a wetting agent, 1-1.5 parts of a defoamer, 0.5-1 parts of a dispersant, and 90-125 parts of deionized water; the base material of the anti-corrosion and wear-resistant layer is one or more of epoxy resin, polyurethane resin, acrylic resin, inorganic zinc-rich coating, inorganic silicate coating, phenolic resin, fluoropolymer emulsion, and polyurea elastomer; the dendritic structure filler is obtained by dispersing, modifying, and compounding zero-dimensional filler, one-dimensional filler, and two-dimensional filler respectively with a dispersion liquid, and the zero-dimensional filler, one-dimensional filler, and two-dimensional filler all obtain reactive sites on the filler surface after modification, and the compounding mass ratio of modified zero-dimensional filler, modified one-dimensional filler, and modified two-dimensional filler is (2-4):1:1.
[0007] This invention is the first to propose and construct a "branch-like structure filler." Addressing the technical bottlenecks of traditional fillers, such as easy agglomeration, weak interfacial bonding with the matrix, and difficulty in forming a synergistic reinforcing effect, this invention specifically modifies zero-dimensional, one-dimensional, and two-dimensional fillers to enrich their surfaces with active functional groups. This allows for uniform dispersion within the matrix, and the fillers cross-link with each other through chemical bonding and non-covalent interactions, forming a branch-like three-dimensional network structure. This structure not only solves the problems of filler dispersion and interfacial bonding but also provides a crucial microstructural foundation for achieving a synergistic improvement in the vibration reduction, corrosion protection, and wear resistance of the coating.
[0008] The dendritic-like structured packing is obtained by compounding zero-dimensional, one-dimensional, and two-dimensional packings after separate modification. After modification, all three packings acquire reactive sites on their surfaces. The mass ratio of the modified zero-dimensional, one-dimensional, and two-dimensional packings is (2~4):1:1. The dendritic-like structured packing of this invention is constructed by combining zero-dimensional, one-dimensional, and two-dimensional packings after specific modification treatments, forming a three-dimensional network structure with interconnected "point-line-surface" relationships.
[0009] The modifiers used for the zero-dimensional filler modification are one or more selected from: 1-methylimidazole, 2-methylimidazole, N-vinylimidazole, 1-butyl-3-methylimidazole tetrafluoroborate ionic liquid, N-methylpyrrolidone, N-ethylpyrrolidone, hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, 4-vinylpyridine, and 2-vinylpyridine. It is understood that the "modifiers" in this invention are all used to modify the filler, increasing its active sites. For ease of use, they can be dispersed in any dispersion solution that is only used for dispersion without affecting its modifying effect.
[0010] The modifiers used for the one-dimensional filler modification are one or more of the following: polystyrene, polyaniline, polyvinylpyrrolidone, poly(N-vinylcarbazole), poly(sodium p-styrene sulfonate), sulfonated polyaniline, chitosan, polydopamine, and lignin sulfonate. The modifiers used for the two-dimensional filler modification are one or more of the following: Pt-Pd core-shell nanoparticles, Au-Ag core-shell nanoparticles, Au@SiO2 core-shell nanoparticles, iron(III) oxide nanoparticles, titanium dioxide nanoparticles, zinc oxide nanoparticles, polystyrene microspheres, polymethyl methacrylate microspheres, ZIF-8MOF nanoparticles, and UiO-66MOF nanoparticles.
[0011] This invention addresses the issues of filler agglomeration and weak interfacial bonding by specifically modifying fillers of different dimensions. Its core principle lies in: zero-dimensional materials, through surface covalent grafting of active functional groups, transform inert surfaces into reactive interfaces, enabling them to participate in the network construction of the resin matrix as chemical crosslinking points; one-dimensional materials, through non-covalent interactions, coat functional polymer layers, these modified layers being rich in active groups, forming strong chemical bonds with the resin matrix and acting as "molecular bridges" connecting other fillers; two-dimensional materials, through in-situ growth and chemical anchoring of polymer microspheres on the surface of the sheets, achieve a "point-to-surface" design, both physically preventing sheet stacking and chemically embedding the two-dimensional material into the overall network. Through these stepwise modifications, inert fillers are transformed into "active fillers" with surfaces rich in reactive functional groups, achieving uniform dispersion in the matrix and chemical / physical crosslinking between them, constructing a three-dimensional dendritic network integrating the "filler-matrix," laying the microstructural foundation for the synergistic improvement of the coating's vibration reduction, corrosion protection, and wear resistance functions.
[0012] Based on the above principles, the coating of the present invention adopts a double-layer composite structure design. The inner layer is a vibration damping layer, which constructs a dendritic structure by introducing modified zero-dimensional, one-dimensional and two-dimensional fillers. The interaction between the fillers and the interfacial friction with the substrate are used to achieve efficient dissipation of vibration energy. The outer layer is an anti-corrosion and wear-resistant layer, which endows the coating with excellent corrosion resistance and wear resistance through a dense cross-linked network and rigid fillers.
[0013] The zero-dimensional filler is selected from at least three of the following: silica nanoparticles, carbon black, nano alumina, nano zinc oxide, nano titanium dioxide, nano gold particles, nano silver particles, nano copper particles, polystyrene microspheres, and polymethyl methacrylate microspheres.
[0014] The one-dimensional filler is selected from at least three of the following: carbon nanotubes, cellulose nanofibers, silicon carbide whiskers, aluminum borate whiskers, calcium sulfate whiskers, silver nanowires, halloysite nanotubes, polyimide nanofibers, and polyacrylonitrile nanofibers.
[0015] The two-dimensional filler is a combination of at least three selected from graphene, graphene derivatives, layered silicates such as montmorillonite, MXene phase materials, hexagonal boron nitride, molybdenum disulfide, tungsten disulfide, and layered double hydroxides.
[0016] The total thickness of the coating is 2~10mm, covering the surface of the substrate, and includes a vibration damping layer and an anti-corrosion and wear-resistant layer from the inside to the outside. The thickness of the vibration damping layer is 1.4~9mm, and the thickness of the anti-corrosion and wear-resistant layer is 0.2~3mm.
[0017] A second aspect of the present invention is to provide a method for preparing the above-mentioned vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base, comprising the following steps: Preparation of A1-type branched structure packing: The zero-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified zero-dimensional packing; the one-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified one-dimensional packing; the two-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified two-dimensional packing; the modified zero-dimensional packing, the modified one-dimensional packing, and the modified two-dimensional packing are mixed and deionized water is added to obtain the dispersion solution of the branched structure packing.
[0018] Preparation of S1 vibration damping layer coating: Take the vibration damping layer substrate material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the reinforced vibration damping layer coating.
[0019] Preparation of S2 anti-corrosion and wear-resistant coating: Take the anti-corrosion and wear-resistant base material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the anti-corrosion and wear-resistant coating.
[0020] Preparation of S3 composite coating: The vibration damping layer coating is sprayed onto the surface of the substrate, the thickness is controlled and cured at room temperature for 24 hours; then the anti-corrosion and wear-resistant layer coating is sprayed, the thickness is controlled and cured at room temperature for 48 hours, thus obtaining the vibration damping, anti-corrosion and wear-resistant composite coating.
[0021] Preferably, in step A1, the zero-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the zero-dimensional filler to the corresponding modifier is 6-8:1. After stirring for 4-5 hours, the mixture is centrifuged, washed, and dried to obtain the modified zero-dimensional filler. The one-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the one-dimensional filler to the corresponding modifier is 5-8:1. After stirring for 24-30 hours, the mixture is centrifuged, washed, and dried to obtain the modified one-dimensional filler. The two-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the two-dimensional filler to the corresponding modifier is 20-25:1. The mixture is ultrasonically dispersed and refluxed at 80-90°C for 6-8 hours. After centrifugation, washing, and drying, the mixture is obtained to obtain the modified two-dimensional filler.
[0022] It is understood that the modifier of the present invention has certain modifying activity and can directly modify the filler through physical dispersion. Under the premise of good dispersion, the amount of modifier added can be reduced to a certain extent.
[0023] Preferably, the substrate is a metal substrate, which is sandblasted before coating to control the surface roughness Rz of the metal substrate to be 50-80 μm. When the substrate is a metal substrate, sandblasting the surface of the substrate before coating improves the adhesion of the coating to the substrate surface.
[0024] The coating of this invention can be applied independently to the traction machine base or used in conjunction with conventional rubber vibration damping pads. It significantly improves the vibration damping effect while also providing long-term corrosion resistance and wear resistance. It overcomes the technical defects of traditional coatings, such as single function, weak interfacial bonding, and uneven filler dispersion, and provides a comprehensive and high-performance solution for the vibration damping problem of elevator traction machines.
[0025] The beneficial effects of this invention are: (1) Constructing a dendritic-like structure packing material to achieve packing-matrix integration: This invention successfully constructed a dendritic-like structure packing material by modifying zero-dimensional, one-dimensional, and two-dimensional packing materials respectively. This structure connects zero-dimensional point-like packing materials, one-dimensional linear packing materials, and two-dimensional sheet-like packing materials into a three-dimensional network through chemical bonding and non-covalent interactions, realizing uniform dispersion and stable anchoring of the packing material in the matrix, and fundamentally solving the technical problems of easy agglomeration and weak interfacial bonding of traditional packing materials.
[0026] (2) Significant vibration reduction performance: The present invention constructs an integrated three-dimensional network of "filler-matrix" in the enhanced vibration reduction layer through a dendritic structure filler. It utilizes the interfacial friction between fillers, the bridging effect of one-dimensional fillers, the interlayer slippage of two-dimensional fillers, and the physicochemical cross-linking with the matrix to achieve multiple dissipation mechanisms for vibration energy, significantly improving the damping performance and vibration reduction effect of the coating, and effectively blocking the transmission of traction machine vibration to the building structure.
[0027] (3) Excellent corrosion resistance and wear resistance: The three-dimensional network formed by the dendritic structure filler of the present invention works synergistically with the dense cross-linked matrix to form an efficient physical barrier, which significantly improves the coating’s ability to block corrosive media; at the same time, the rigid zero-dimensional filler, the toughened one-dimensional filler and the lubricating two-dimensional filler work synergistically during the friction process, giving the coating excellent wear resistance and extending the service life of the coating.
[0028] (4) Reasonable structural design and flexible application: The present invention adopts a double-layer composite structure design, which can adjust the thickness ratio of each layer according to the actual working conditions to achieve performance control as needed; the coating can be used independently or in combination with traditional rubber vibration damping pads, which has strong adaptability and good engineering application prospects. Attached Figure Description
[0029] Figure 1 This is a transmission electron microscope (TEM) image of the branch-like structure filler in Embodiment 1 of the present invention. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] See Figure 1 This invention provides a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base. The coating covers the surface of a substrate and has a double-layer composite structure. From the inside to the outside of the substrate surface, the coating sequentially includes a vibration-damping layer and a corrosion-resistant and wear-resistant layer. By weight, the raw materials of the vibration-damping layer include 70-80 parts of vibration-damping layer base material, 10-15 parts of dendritic filler, 1-2.5 parts of wetting agent, 1-3 parts of defoamer, 1.5-2 parts of dispersant, and 90-125 parts of deionized water. The vibration-damping layer base material is one of polyurethane-based IPN emulsion, epoxy resin-based IPN emulsion, acrylate-based IPN emulsion, silicone-based IPN emulsion, and fluoropolymer-based IPN emulsion.
[0032] The raw materials of the anti-corrosion and wear-resistant layer include 30-40 parts of anti-corrosion and wear-resistant layer base material, 5-10 parts of dendritic structure filler, 1-1.5 parts of wetting agent, 0.5-1 part of defoamer, 0.5-1 part of dispersant, and 90-125 parts of deionized water; the anti-corrosion and wear-resistant layer base material is one or more of epoxy resin, polyurethane resin, acrylic resin, inorganic zinc-rich coating, inorganic silicate coating, phenolic resin, fluoropolymer emulsion, and polyurea elastomer.
[0033] The dendritic structure packing is obtained by dispersing, modifying and compounding zero-dimensional packing, one-dimensional packing and two-dimensional packing respectively with dispersion liquid. After modification, the zero-dimensional packing, one-dimensional packing and two-dimensional packing all obtain reactive sites on the surface of the packing. The mass ratio of the modified zero-dimensional packing, modified one-dimensional packing and modified two-dimensional packing is (2~4):1:1.
[0034] The modifiers used for the zero-dimensional filler modification are one or more of the following: 1-methylimidazolium, 2-methylimidazolium, N-vinylimidazolium, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, N-methylpyrrolidone, N-ethylpyrrolidone, hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, 4-vinylpyridine, and 2-vinylpyridine; the modifiers used for the one-dimensional filler modification are: polystyrene, polyaniline, polyvinylpyrrolidone, poly(N-vinylcarbazole), and poly(p-styrene). The modifier used for the modification of the two-dimensional filler is one or more of the following: sodium sulfonate, sulfonated polyaniline, chitosan, polydopamine, and lignin sulfonate; the modifier used for the modification of the two-dimensional filler is one or more of the following: Pt-Pd core-shell structured nanoparticles, Au-Ag core-shell structured nanoparticles, Au@SiO2 core-shell structured nanoparticles, iron tetroxide nanoparticles, titanium dioxide nanoparticles, zinc oxide nanoparticles, polystyrene microspheres, polymethyl methacrylate microspheres, ZIF-8MOF nanoparticles, and UiO-66MOF nanoparticles.
[0035] The zero-dimensional filler is selected from at least three of the following: silica nanoparticles, carbon black, nano alumina, nano zinc oxide, nano titanium dioxide, nano gold particles, nano silver particles, nano copper particles, polystyrene microspheres, and polymethyl methacrylate microspheres.
[0036] The one-dimensional filler is selected from at least three of the following: carbon nanotubes, cellulose nanofibers, silicon carbide whiskers, aluminum borate whiskers, calcium sulfate whiskers, silver nanowires, halloysite nanotubes, polyimide nanofibers, and polyacrylonitrile nanofibers.
[0037] The two-dimensional filler is a combination of at least three selected from graphene, graphene derivatives, layered silicates such as montmorillonite, MXene phase materials, hexagonal boron nitride, molybdenum disulfide, tungsten disulfide, and layered double hydroxides.
[0038] The total thickness of the coating is 2~10mm, wherein the thickness of the vibration damping layer is 1.4~9mm, and the thickness of the anti-corrosion and wear-resistant layer is 0.2~3mm.
[0039] A method for preparing a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base includes the following steps: Preparation of A1 type branched structure filler: The zero-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the zero-dimensional filler to the corresponding modifier is 6~8:1. After stirring for 4~5 hours, the mixture is centrifuged, washed, and dried to obtain the modified zero-dimensional filler. The one-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the one-dimensional filler to the corresponding modifier is 5~8:1. After stirring for 24~30 hours, the mixture is centrifuged, washed, and dried to obtain the modified zero-dimensional filler. The two-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the two-dimensional filler to the corresponding modifier is 20~25:1. The mixture is ultrasonically dispersed and refluxed at 80~90℃ for 6~8 hours. After centrifugation, washing, and drying, the mixture is obtained.
[0040] Preparation of S1 vibration damping layer coating: Take the vibration damping layer substrate material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the reinforced vibration damping layer coating.
[0041] Preparation of S2 anti-corrosion and wear-resistant coating: Take the anti-corrosion and wear-resistant base material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the anti-corrosion and wear-resistant coating.
[0042] Preparation of S3 composite coating: The vibration damping layer coating is sprayed onto the surface of a sandblasted metal substrate, the surface roughness Rz of the metal substrate is controlled to be 50-80μm, the coating thickness is controlled and cured at room temperature for 24h; then the anti-corrosion and wear-resistant layer coating is sprayed onto the surface of the metal substrate, the thickness is controlled and cured at room temperature for 48h, thus obtaining a vibration damping, anti-corrosion and wear-resistant composite coating.
[0043] Example 1
[0044] This embodiment 1 provides a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base, and its preparation method is as follows: Preparation of A1 type branched structure filler: Take 30g of zero-dimensional filler silica nanoparticles, nano alumina and polystyrene microspheres (mass ratio 1:1:1), add 5g of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, stir and react at 60℃ for 4h, centrifuge, wash and dry to obtain modified zero-dimensional filler.
[0045] Take 10g of one-dimensional filler carbon nanotubes, silicon carbide whiskers and halloysite nanotubes (mass ratio 1:1:1), disperse them in Tris-HCl buffer (pH=8.5), add 2g of dopamine hydrochloride, stir at room temperature for 24h, centrifuge, wash and dry to obtain polydopamine-coated one-dimensional filler.
[0046] Take 10g of two-dimensional filler graphene, hexagonal boron nitride and molybdenum disulfide (mass ratio 1:1:1), disperse them in ethanol, add 50mL of Au@SiO2 core-shell structured nanoparticle dispersion (solid content 1%, mass about 0.5g), ultrasonically disperse, reflux at 80℃ for 6h, centrifuge, wash and dry to obtain Au@SiO2 “point-to-surface” anchored modified two-dimensional filler.
[0047] The modified zero-dimensional filler (30g), one-dimensional filler (10g) and two-dimensional filler (10g) were mixed in a mass ratio of 3:1:1, and 100mL of deionized water was added. The mixture was ultrasonically dispersed for 30min to obtain a dendritic-like structured filler dispersion.
[0048] Preparation of S1 vibration damping layer coating: Take 70 parts of polyurethane-based IPN emulsion as the base material of the vibration damping layer, add 15 parts of the dendritic structure filler dispersion obtained in step A1 (based on filler solid content), 2.5 parts of wetting agent (polyether modified siloxane), 2 parts of defoamer (modified polysiloxane), 1.5 parts of dispersant (polymeric superdispersant), and 100 parts of deionized water, stir and disperse evenly, and degas under vacuum to obtain the vibration damping layer coating.
[0049] Preparation of S2 anti-corrosion and wear-resistant coating: Take 30 parts of epoxy resin and fluoropolymer emulsion (mass ratio 2:1) as the base material of the anti-corrosion and wear-resistant layer, add 5 parts of dendritic structure filler dispersion (based on filler solid content), 1 part of wetting agent, 0.5 parts of defoamer, 0.5 parts of dispersant, and 100 parts of deionized water, stir and disperse evenly, and degas under vacuum to obtain the anti-corrosion and wear-resistant coating.
[0050] Preparation of S3 composite coating: The above-mentioned vibration damping layer coating is sprayed onto the surface of a sandblasted metal substrate, with a thickness of 4.0 mm, and cured at room temperature for 24 h; then, an enhanced anti-corrosion and wear-resistant layer coating is sprayed onto its surface, with a thickness of 1.0 mm, and cured at room temperature for 48 h, thus obtaining a composite coating with a total thickness of 5.0 mm.
[0051] The metal substrate used in this embodiment 1 is: substrate grade: Q235B; structural steel; length*width*height: 800mm×500mm×14mm.
[0052] Example 2
[0053] This embodiment 2 is basically the same as embodiment 1, except that the mass ratio of the zero-dimensional, one-dimensional and two-dimensional fillers of the branch-like structure filler is 2:1:1.
[0054] Example 3
[0055] This embodiment 3 is basically the same as embodiment 1, except that the mass ratio of the zero-dimensional, one-dimensional and two-dimensional fillers of the branch-like structure filler is 4:1:1.
[0056] Example 4
[0057] This embodiment 4 is basically the same as embodiment 1, except that the base material of the vibration damping layer is epoxy resin-based IPN emulsion, and the base material of the anti-corrosion and wear-resistant layer is polyurethane resin.
[0058] Example 5
[0059] Example 5 is basically the same as Example 1, except that the zero-dimensional filler uses a combination of nano zinc oxide, nano titanium dioxide and carbon black (mass ratio 1:1:1); the one-dimensional filler uses a combination of aluminum borate whiskers, calcium sulfate whiskers and polyimide nanofibers (mass ratio 1:1:1); and the two-dimensional filler uses a combination of montmorillonite, MXene and layered double hydroxides (mass ratio 1:1:1).
[0060] Example 6
[0061] This embodiment 6 is basically the same as embodiment 1, except that the total coating thickness is 2mm, of which the thickness of the enhanced vibration damping layer is 1.4mm (accounting for 70%) and the thickness of the enhanced anti-corrosion and wear-resistant layer is 0.6mm.
[0062] Example 7
[0063] This embodiment 7 is basically the same as embodiment 1, except that the total coating thickness is 10mm, of which the vibration damping layer is 9mm thick (accounting for 90%) and the anti-corrosion and wear-resistant layer is 1mm thick.
[0064] Example 8
[0065] Example 8 is basically the same as Example 1, except that: the base material of the vibration damping layer is an acrylic ester-based IPN emulsion; and the base material of the anti-corrosion and wear-resistant layer is an acrylic resin. The other raw material types, proportions, and preparation processes are the same as in Example 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0066] Example 9
[0067] Example 9 is basically the same as Example 1, except that: the vibration damping layer substrate material is an organosilicon-based IPN emulsion; and the anti-corrosion and wear-resistant layer substrate material is an inorganic zinc-rich coating. The other raw material types, proportions, and preparation processes are the same as in Example 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0068] Example 10
[0069] Example 10 is basically the same as Example 1, except that: the base material of the vibration damping layer is a fluoropolymer-based IPN emulsion; and the base material of the anti-corrosion and wear-resistant layer is a phenolic resin. The other raw material types, proportions, and preparation processes are the same as in Example 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0070] Example 11
[0071] This embodiment 11 is basically the same as embodiment 1, except that: the base material of the vibration damping layer is a polyurethane-based IPN emulsion (the same as in embodiment 1); and the base material of the anti-corrosion and wear-resistant layer is a polyurea elastomer. The other raw material types, proportions, and preparation processes are the same as in embodiment 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0072] Example 12
[0073] Example 12 is basically the same as Example 1, except that: the substrate material of the vibration damping layer is an epoxy resin-based IPN emulsion (the same as in Example 4); and the substrate material of the anti-corrosion and wear-resistant layer is an inorganic silicate coating. The other raw material types, proportions, and preparation processes are the same as in Example 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0074] Example 13
[0075] Example 13 is basically the same as Example 1, except that: the base material of the vibration damping layer is an acrylic ester-based IPN emulsion; and the base material of the anti-corrosion and wear-resistant layer is a fluoropolymer emulsion (pure emulsion, not IPN). The other raw material types, ratios, and preparation processes are the same as in Example 1, resulting in a composite coating with a total thickness of 5.0 mm.
[0076] Comparative Example 1
[0077] Comparative Example 1 is basically the same as Example 1, except that no branch-like filler is added, and both the vibration damping layer and the anti-corrosion and wear-resistant layer are pure resin coatings.
[0078] Comparative Example 2
[0079] Comparative Example 2 is basically the same as Example 1, except that the dendritic structure packing uses only zero-dimensional packing (a mixture of silica nanoparticles, nano-alumina, and polystyrene microspheres, after the same modification treatment), without adding one-dimensional or two-dimensional packing.
[0080] Comparative Example 3
[0081] Comparative Example 3 is basically the same as Example 1, except that the dendritic structure filler uses only one-dimensional filler (a mixture of carbon nanotubes, silicon carbide whiskers, and halloysite nanotubes, after the same modification treatment), without adding zero-dimensional and two-dimensional fillers.
[0082] Comparative Example 4
[0083] Comparative Example 4 is basically the same as Example 1, except that the dendritic structure packing uses only two-dimensional packing (a mixture of graphene, hexagonal boron nitride, and molybdenum disulfide, after the same modification treatment), without adding zero-dimensional and one-dimensional packing.
[0084] Comparative Example 5
[0085] Comparative Example 5 is basically the same as Example 1, except that the zero-dimensional, one-dimensional, and two-dimensional fillers are of the same type and ratio as in Example 1, but no modification is performed and they are directly mixed and used.
[0086] Comparative Example 6
[0087] Comparative Example 6 is basically the same as Example 1, except that the zero-dimensional, one-dimensional, and two-dimensional fillers are of the same type and ratio as in Example 1, but they are not subject to targeted modification treatment and are directly added to the matrix after physical mixing.
[0088] Comparative Example 7
[0089] Comparative Example 7 is basically the same as Example 1, except that it does not use a double-layer composite structure. Instead, the raw materials of the enhanced vibration damping layer and the enhanced corrosion and wear-resistant layer are mixed and coated in one step, with a total thickness of 5 mm.
[0090] Performance testing
[0091] The coatings prepared in Examples 1-13 and Comparative Examples 1-7 were subjected to the following performance tests, and the results are shown in Table 1.
[0092] Test method: (1) Vibration reduction performance: The loss factor (tanδ) of the coating was tested using a dynamic mechanical analyzer (DMA) at a temperature of 25℃ and a frequency of 10Hz. The larger the loss factor, the better the vibration reduction performance.
[0093] (2) Corrosion resistance: The low-frequency impedance modulus (|Z| 0.01 Hz) of the coating in 3.5 wt% NaCl solution was tested by electrochemical impedance spectroscopy (EIS) for 72 h. The larger the |Z| 0.01 Hz value, the better the corrosion resistance.
[0094] (3) Abrasion resistance: The abrasion resistance of the coating was tested using a Taber abrasion tester with a load of 1000g, a CS-17 grinding wheel, and a rotation speed of 1000r. The abrasion loss (mg) was recorded. The smaller the abrasion loss, the better the abrasion resistance.
[0095] (4) Adhesion: The adhesion between the coating and the substrate (MPa) is tested by the pull-off method, in accordance with GB / T 5210 standard.
[0096] Table 1. Coating performance test results of the examples and comparative examples.
[0097] The test results in Table 1 show that: 1. The coatings prepared in Examples 1-13 of the present invention have significantly better loss factor, low-frequency impedance modulus, wear amount and adhesion than the comparative examples, indicating that the elevator traction machine base coating provided by the present invention, which has the functions of vibration reduction, corrosion protection and wear resistance, has excellent comprehensive performance.
[0098] 2. Comparing Example 1 with Comparative Examples 1-4, it can be seen that the coating with added dendritic structure filler (zero-dimensional, one-dimensional, and two-dimensional composite) has significantly better vibration reduction, corrosion resistance, and wear resistance than the coating without filler or the coating with only single-dimensional filler. This indicates that the dendritic structure constructed by the "zero-one-two" multi-dimensional filler composite has a significant synergistic enhancement effect.
[0099] 3. Comparing Example 1 with Comparative Examples 5-6, it can be seen that the dendritic structure constructed by the targeted modification of the filler has better performance than the unmodified or simply mixed filler. This indicates that the stepwise modification of zero-dimensional, one-dimensional, and two-dimensional fillers in this invention is the key to constructing a stable dendritic structure and realizing the integration of filler and matrix.
[0100] 4. Comparing Example 1 and Comparative Example 7, it can be seen that the coating with a double-layer composite structure design has better performance than the single-layer hybrid structure. This indicates that designing the vibration reduction function and the anti-corrosion and wear-resistant function in layers is conducive to the full utilization of the functions of each layer and avoids mutual restriction of functions.
[0101] 5. The comparison of Examples 1-3 shows that the mass ratio of zero-dimensional, one-dimensional, and two-dimensional fillers affects the coating performance. When the ratio is 3:1:1 (Example 1), the overall performance is optimal.
[0102] 6. Comparing Examples 1, 4, and 8-13, it can be seen that, under the premise of keeping the core-type branch structure filler and preparation process unchanged, replacing the substrate material of the vibration damping layer with acrylate-based IPN emulsion (Example 8), silicone-based IPN emulsion (Example 9), or fluoropolymer-based IPN emulsion (Example 10), or replacing the substrate material of the anti-corrosion and wear-resistant layer with inorganic zinc-rich coating (Example 9), phenolic resin (Example 10), polyurea elastomer (Example 11), inorganic silicate coating (Example 12), or fluoropolymer emulsion (Example 13), the resulting coatings can all maintain excellent comprehensive performance.
[0103] 7. When the anti-corrosion and wear-resistant layer uses an inorganic silicate coating (Example 12), the coating exhibits the highest low-frequency impedance modulus and the lowest wear, demonstrating excellent anti-corrosion and wear-resistant properties; when the vibration damping layer uses a polyurethane-based IPN emulsion and the anti-corrosion layer uses a polyurea elastomer (Example 11), the coating exhibits the highest loss factor, demonstrating the best vibration damping effect.
[0104] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.
Claims
1. A vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base, wherein the coating covers the surface of a substrate, characterized in that: The coating has a double-layer composite structure. From the inside to the outside of the substrate surface, the coating sequentially includes a vibration damping layer and an anti-corrosion and wear-resistant layer. By weight, the raw materials of the vibration damping layer include 70-80 parts of vibration damping layer base material, 10-15 parts of dendritic filler, 1-2.5 parts of wetting agent, 1-3 parts of defoamer, 1.5-2 parts of dispersant, and 90-125 parts of deionized water. The vibration damping layer base material is one of polyurethane-based IPN emulsion, epoxy resin-based IPN emulsion, acrylate-based IPN emulsion, silicone-based IPN emulsion, and fluoropolymer-based IPN emulsion. The raw materials for the anti-corrosion and wear-resistant layer include 30-40 parts of anti-corrosion and wear-resistant layer base material, 5-10 parts of dendritic structure filler, 1-1.5 parts of wetting agent, 0.5-1 part of defoamer, 0.5-1 part of dispersant, and 90-125 parts of deionized water; the anti-corrosion and wear-resistant layer base material is one or more of epoxy resin, polyurethane resin, acrylic resin, inorganic zinc-rich coating, inorganic silicate coating, phenolic resin, fluoropolymer emulsion, and polyurea elastomer. The dendritic structure packing is obtained by dispersing, modifying and compounding zero-dimensional packing, one-dimensional packing and two-dimensional packing respectively with dispersion liquid. After modification, the zero-dimensional packing, one-dimensional packing and two-dimensional packing all obtain reactive sites on the surface of the packing. The mass ratio of the modified zero-dimensional packing, modified one-dimensional packing and modified two-dimensional packing is (2~4)∶1∶1. The modifier used for the zero-dimensional filler modification is one or more of the following: 1-methylimidazolium, 2-methylimidazolium, N-vinylimidazolium, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, N-methylpyrrolidone, N-ethylpyrrolidone, hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, 4-vinylpyridine, and 2-vinylpyridine. The modifier used for the one-dimensional filler modification is one or more of the following: polystyrene, polyaniline, polyvinylpyrrolidone, poly-N-vinylcarbazole, sodium terephthalate sulfonate, sulfonated polyaniline, chitosan, polydopamine, and lignin sulfonate. The modifier used for the two-dimensional filler modification is one or more of the following: Pt-Pd core-shell nanoparticles, Au-Ag core-shell nanoparticles, Au@SiO2 core-shell nanoparticles, iron tetroxide nanoparticles, titanium dioxide nanoparticles, zinc oxide nanoparticles, polystyrene microspheres, polymethyl methacrylate microspheres, ZIF-8MOF nanoparticles, and UiO-66MOF nanoparticles.
2. The vibration-damping, corrosion-resistant, and wear-resistant coating for elevator traction machine base according to claim 1, characterized in that: The zero-dimensional filler is selected from at least three of the following: silica nanoparticles, carbon black, nano alumina, nano zinc oxide, nano titanium dioxide, nano gold particles, nano silver particles, nano copper particles, polystyrene microspheres, and polymethyl methacrylate microspheres.
3. The vibration-damping, corrosion-resistant, and wear-resistant coating for the elevator traction machine base according to claim 1, characterized in that: The one-dimensional filler is selected from at least three of the following: carbon nanotubes, cellulose nanofibers, silicon carbide whiskers, aluminum borate whiskers, calcium sulfate whiskers, silver nanowires, halloysite nanotubes, polyimide nanofibers, and polyacrylonitrile nanofibers.
4. The vibration-damping, corrosion-resistant, and wear-resistant coating for the elevator traction machine base according to claim 1, characterized in that: The two-dimensional filler is selected from at least three combinations of graphene, graphene derivatives, montmorillonite, MXene phase materials, hexagonal boron nitride, molybdenum disulfide, tungsten disulfide, and layered double hydroxides.
5. The vibration-damping, corrosion-resistant, and wear-resistant coating for the elevator traction machine base according to claim 1, characterized in that: The total thickness of the coating is 2~10mm, wherein the thickness of the vibration damping layer is 1.4~9mm, and the thickness of the anti-corrosion and wear-resistant layer is 0.2~3mm.
6. The method for preparing the vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base as described in any one of claims 1-5, characterized in that: Includes the following steps: Preparation of A1-type branched structure packing: The zero-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified zero-dimensional packing; the one-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified one-dimensional packing; the two-dimensional packing is dispersed in a dispersion solution and then modified with a modifier to obtain the modified two-dimensional packing; the modified zero-dimensional packing, the modified one-dimensional packing, and the modified two-dimensional packing are mixed and deionized water is added to obtain the dispersion solution of the branched structure packing; Preparation of S1 vibration damping layer coating: Take the vibration damping layer substrate material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the reinforced vibration damping layer coating. Preparation of S2 anti-corrosion and wear-resistant coating: Take the anti-corrosion and wear-resistant base material, add the dispersion of the dendritic structure filler, the wetting agent, the defoamer, the dispersant, and the deionized water, stir and disperse evenly, and degas under vacuum to obtain the anti-corrosion and wear-resistant coating. Preparation of S3 composite coating: The vibration damping layer coating is sprayed onto the surface of the substrate, the thickness is controlled and cured at room temperature for 24 hours; then the anti-corrosion and wear-resistant layer coating is sprayed, the thickness is controlled and cured at room temperature for 48 hours, thus obtaining the vibration damping, anti-corrosion and wear-resistant composite coating.
7. The method for preparing a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base according to claim 6, characterized in that: In step A1, the zero-dimensional filler is dispersed in a dispersion liquid and then modified with a modifier. The mass ratio of the zero-dimensional filler to its corresponding modifier is 6-8:
1. After stirring and reacting for 4-5 hours, the mixture is centrifuged, washed, and dried to obtain the modified zero-dimensional filler. The one-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the one-dimensional filler to its corresponding modifier is 5-8:
1. After stirring and reacting for 24-30 hours, the mixture is centrifuged, washed, and dried to obtain the modified one-dimensional filler. The two-dimensional filler is dispersed in a dispersion solution and then modified with a modifier. The mass ratio of the two-dimensional filler to its corresponding modifier is 20~25:
1. After ultrasonic dispersion and reflux reaction at 80~90℃ for 6~8h, the mixture is centrifuged, washed, and dried to obtain the modified two-dimensional filler.
8. The method for preparing a vibration-damping, corrosion-resistant, and wear-resistant coating for an elevator traction machine base according to claim 6, characterized in that: The substrate is a metal substrate, which is sandblasted before being coated with paint, and the surface roughness Rz of the metal substrate is controlled to be 50-80μm.
Citation Information
Patent Citations
Preparation and application of restrained-structure water-based damping coating with wideband and wide-temperature range
CN106810981A
Coating for wind power blade and preparation method thereof
CN122127867A